Assessing the Use of Pumice in Water Treatment Case Study of the Shuuku- Masyoro Gravity Flow Scheme - Trevor Ezekiel Mupere (Uganda Christian University, 2025)
Excessive iron concentrations in water supply systems pose significant health and operational challenges, particularly in rural gravity flow systems. This study evaluates the effectiveness of thermally activated pumice as a low-cost adsorbent for the removal of dissolved iron at the Shuuku-Masyoro gravity flow scheme in Sheema district, Uganda, where the iron levels are up to 1.32mg/L exceeding the set permissible limits by the World Health Organization of 0.3mg/L. Through batch adsorption experiments, Langmuir isotherm analysis and prototype testing, the study demonstrated that pumice that was thermally activated at 6000C achieves a maximum adsorption capacity of 26.53mg/g, reducing the iron concentrations in the water by over 80%. The key findings showed that iron removal by adsorption either occurs through the mechanism of surface complexation or ion exchange, with the optimal performance of the proposed material attained using a 1.8kg pumice filter bed at a hydraulic loading rate of 5.88m/hr. Seasonal variations were observed, with the efficiency in the dry season being impacted by the ground water alkalinity and reduced dilution at the river kyarweera, which is the where the water is abstracted from. The proposed adsorption tank integrates these parameters, which offered a scalable, energy-efficient alternative to conventional aeration methods. This research underscores the potential of pumice as a sustainable adsorbent and filtration medium for iron-rich water in the gravity flow schemes. The recommendations include further studies on chemical activation and regeneration of adsorbents to enhance the cost effectiveness and the durability of the material during operation of the scheme.
Undergraduate